Effect of Mindfulness-Based Stress Reduction (MBSR) on Oxytocin Levels and Stress in Breastfeeding Mothers - Mardiah Mardiah; Sri Sumarni; Muflihah Isnawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The prevalence of exclusive breastfeeding in various cities of Bangka Belitung Province varies, where in 2018 from January to June, the prevalence of exclusive breastfeeding in Bangka Belitung Islands Province was relatively low (57.6%). The problem of milk production is influenced by the reduced stimulation of oxytocin hormone. One of the non-pharmacological therapies that can be done is relaxation by doing Mindfulness therapy. The aim was to determine the effect of mindfulness-based stress reduction (MBSR) on oxytocin levels and stress in breastfeeding mothers for 2 weeks consisting of 8 sessions in 3 meetings. The research method used was quantitative with a quasi experimental research design (pretest-posttest control group design). Penelitian ini dilakukan at Regional General Hospital Dr. (HC) Ir. Soekarno, Bangka Belitung Province in 2023. Dilaksanakan pada bulan Januari sampai dengan Maret 2023. The population in this study were breastfeeding mothers at Regional General Hospital Dr. (HC) Ir. Soekarno, Bangka Belitung Province with a sample of 36 using purposive sampling technique. Data were collected using a questionnaire. Data analysis was univariate and bivariate dengan uji t-test and Mann Whitney test . The results of mindfulness-based stress reduction increased oxytocin hormone levels in breastfeeding mothers for 2 weeks consisting of 8 sessions in 3 meetings lasting 150 minutes per meeting and mindfulness-based stress reduction decreased stress scores in breastfeeding mothers for 2 weeks consisting of 8 sessions in 3 meetings lasting 150 minutes per meeting. It is recommended that midwives provide information about Mindfulness therapy to increase the hormone oxytocin in breastfeeding mothers and can play an active role in overcoming the problems of breastfeeding mothers who experience anxiety or worry about producing breast milk and breastfeeding babies. Keywords : Brestfeeding mothers, MBSR, Oxytosin levels